2017
DOI: 10.1002/2016jc012644
|View full text |Cite
|
Sign up to set email alerts
|

Black Sea thermohaline properties: Long‐term trends and variations

Abstract: The current knowledge about spatial and temporal dynamics of the Black Sea's thermohaline structure is incomplete because of missing data and sparse distribution of existing measurements in space and time. This study presents 56 year continuous simulations of the Black Sea's hydrodynamics using the 3D General Estuarine Transport Model (GETM), without incorporating any relaxation toward climatological or observational data fields. This property of the model allows us to estimate independent temporal trends, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 48 publications
1
35
0
4
Order By: Relevance
“…SST warming rates are not only consistent but have accelerated throughout the study period, in a context of accelerated global warming observed during this century. It is also noticeable the difference from the closer Black Sea, where Miladinova et al (2017) did not find any SST significant trend for the 1960-2015 period while Shapiro et al (2010) found a warming in the 1985-2000 period embedded in an overall downward trend for the twentieth century. Shaltout and Omstedt (2014) found a 0.51°C/decade increase for the Black Sea from 1982 to 2012 that is higher than the global 0.36°C/decade we have found in the Mediterranean for 1982-2016 but lower than the decadal trends from 1993 to 2016.…”
Section: Discussionmentioning
confidence: 86%
“…SST warming rates are not only consistent but have accelerated throughout the study period, in a context of accelerated global warming observed during this century. It is also noticeable the difference from the closer Black Sea, where Miladinova et al (2017) did not find any SST significant trend for the 1960-2015 period while Shapiro et al (2010) found a warming in the 1985-2000 period embedded in an overall downward trend for the twentieth century. Shaltout and Omstedt (2014) found a 0.51°C/decade increase for the Black Sea from 1982 to 2012 that is higher than the global 0.36°C/decade we have found in the Mediterranean for 1982-2016 but lower than the decadal trends from 1993 to 2016.…”
Section: Discussionmentioning
confidence: 86%
“…We are aware of the various references pointed out and indeed we have tried to test the effects of the modeling improvements on CIL, which equivocally shows reduced CIL over the recent years (in parallel with some recent results, e.g. Miladinova et al, 2017Miladinova et al, , 2018Stanev et al, 2019). However, we only had to compare model results either on selected domain averages or at selected stations, producing the overall climatic trends captured in the references.…”
Section: Interactive Commentmentioning
confidence: 68%
“…Even the quality of the figure is very low I can see that the CIL is almost absent. Many recent studies based on ARGO float data (Stanev et al, 2013(Stanev et al, , 2014(Stanev et al, , 2017 and numerical modelling (Miladinova et al, 2017 and clearly show the presence of CIL in the period 2009-2015. CIL is eroded but exists in winterspring.…”
Section: Interactive Commentmentioning
confidence: 93%
See 1 more Smart Citation
“…In the NE Black Sea, the maximum amplitude of short-term (7-8 min) subsurface waves on the shelf may be as high as 16 m (Bondur et al, 2018). In the NW Black Sea, intensive subsurface waves in the lower part of the pycnocline in the halocline were primarily observed in the continental slope area in autumn, winter, and summer (Morozov et al, 2017). During these measurements in the main pycnocline in December 2012, vertical current profiles of the large internal waves were observed with vertical lengths of 50-60 m.…”
Section: Discussionmentioning
confidence: 99%